Estimating the historical impact of outbreak response immunisation programmes across 210 outbreaks in low and middle-income countries - Stefanie Vaccher; Romesh G Abeysuriya; Nick Scott; Dominic Delport; Tewodaj Mengistu; Alina M Muellenmeister; Gabrielle MacKechnie; Dan Hogan (BMJ Global Health)
Background Outbreaks of vaccine-preventable diseases frequently occur in low and middle-income countries (LMICs), requiring outbreak response immunisation (ORI) programmes for containment. To inform future investment decisions, this study aimed to estimate the cases, deaths, disability-adjusted life years (DALYs) and societal economic costs averted by past ORI programmes. Outbreaks of measles, Ebola, yellow fever, cholera and meningococcal meningitis in LMICs between 2000 and 2023 were considered.Methods 210 outbreaks (51 measles, 40 cholera, 88 yellow fever, 24 meningitis, 7 Ebola) across 49 LMICs were identified with sufficient data for analysis. Data were sourced from publicly available outbreak reports and literature. Agent-based models were calibrated for each disease such that after controlling for baseline vaccine coverage, response time, vaccination rate, environmental variables or endemic prevalence of the disease, observed outbreaks were within the distribution of simulated outbreaks. A status-quo and no ORI scenario were compared for each outbreak.Findings Across 210 outbreaks, ORI programmes are estimated to have averted 5.81M (95% uncertainty interval 5.75M–5.87M) cases (4.01M measles, 283K cholera, 1.50M yellow fever, 21.3K meningitis, 820 Ebola), 327K (317K–338K) deaths (20.0K measles, 5215 cholera, 300K yellow fever, 1599 meningitis, 381 Ebola), 14.6M (14.1M–15.1M) DALYs (1.27M measles, 220K cholera, 13.0M yellow fever, 113K meningitis, 16.6K Ebola) and US$31.7B (29.0B–34.9B) (US$710M measles, US$156M cholera, US$30.7B yellow fever, US$97.6M meningitis, US$6.72M Ebola) in economic costs. Often, the more rapidly the ORI was initiated the greater impact.Interpretation ORI programmes are critical for reducing the health and economic impacts of outbreaks of vaccine-preventable diseases.